2020
DOI: 10.1155/2020/6759346
|View full text |Cite
|
Sign up to set email alerts
|

siRNA Design to Silence the 3UTR Region of Zika Virus

Abstract: The disease caused by the Zika virus (ZIKV) has positioned itself as one of the main public health problems in Mexico. One of the main reasons is it causes microcephaly and other birth defects. The transmission of ZIKV is through Aedes aegypti and Ae. albopictus mosquitoes, which are found in a larger space of the national territory. In addition, it can also be transmitted via blood transfusion, sexual relations, and maternal-fetal route. So far, there are no vaccines or specific treatments to deal with this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The long-term treatment of HCV replicon cells also did not lead to the emergence of escape mutant viruses which ensured the sustained effectiveness of the antiviral therapy over an extended time period [19]. We developed a novel in silico pipeline for predicting and validating siRNA molecules that combines multiple effective in silico methods used in the previous studies [38,39,23,19], which demonstrated successful inhibition of viral replication in vitro. This innovative pipeline con dently aims to identify and validate siRNAs with the potential to inhibit viral replication in in vitro experiments (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term treatment of HCV replicon cells also did not lead to the emergence of escape mutant viruses which ensured the sustained effectiveness of the antiviral therapy over an extended time period [19]. We developed a novel in silico pipeline for predicting and validating siRNA molecules that combines multiple effective in silico methods used in the previous studies [38,39,23,19], which demonstrated successful inhibition of viral replication in vitro. This innovative pipeline con dently aims to identify and validate siRNAs with the potential to inhibit viral replication in in vitro experiments (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…The tertiary structures of guide strands of nal 17 siRNA molecules, which passed the validation criteria were modelled and viewed using UCSF Chimera 1.16 (Fig. [21][22][23][24][25][26][27]. The 3D models obtained were further validated using MolProbity server (Additional le 1: Table S8).…”
Section: Secondary Structure Prediction and Minimum Free Energy Deter...mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have proved that the efficiency of different siRNAs against the same target gene can be different; confirming that the random design of siRNAs is not a valid strategy when it comes to obtaining efficient inhibitors. One of the critical rules to take into account is related to the folding and accessibility of the target region [6][7][8][9][10]. Many of the highly conserved regions in viral genomes, which show a compact folding, can be refractory to siRNA targeting.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, there are reports available on the in silico design of siRNAs against different human viruses, e.g., Zika virus [14][15][16], MERS-CoV [17][18][19], Influenza virus [20][21][22], human adenovirus type-3 [23], hepatitis C virus [24], rabies virus [25], and respiratory syncytial virus [26]. siRNAs designed in silico from a majority of the studies mentioned above were tested in vitro and were found to be effective [14,[17][18][19][20][21][22]24]. A comprehensive review on the usage of siRNA for gene silencing of coronaviruses is given in Sajid et al [4] and Uludag et al [27].…”
mentioning
confidence: 99%